Determining factors for aterial hypertension program desertion. Chiclayo Almanzor Aguinaga Asenjo National Hospital, ESSALUD 2000 - Soto, Víctor (2002)
Objetives: To determine the main factors for desertion from the Arterial Hypertension Program. Setting: Chiclayo Almanzor Aguinaga National Hospital. Design: Analytical case-control study. Material and methods: Cases were 126 patients who deserted for over 6 months and controls the 252 patients who continued in the program, paired for sex, age, place of referral and hypertension level; patients with complications or adscription changes were excluded. A domiciliary survey was applied. Results: Low knowledge about hypertension was the main factor (OR: 15.31), including desinterest in monthly control (OR: 14,6), treatment negligence when both arterial blood pressure returned to normality (OR: 13,8) or when asymptomatic (OR: 13,2), all meaning inappropiate illness consciousness. Other factors found were: No change in life style (OR: 4,5), and colateral drug effects (OR: 1,9); there was no association with professional mistreatment, overcrowding, discomfort, inadequate schedule or patient’s economical or translation problems. Conclusion: Inadequate knowledge on arterial hypertension was de determinant factor for Arterial Hypertension Program desertion at EsSalud Almanzor Aguinaga Asenjo National Hospital.